Spirituality Level, Family Support, and Spiritual Self Care Behavior among Patient with Diabetic Ulcers - Pratiwi, Ika Nur; Kusnanto, Kusnanto; Putri, Malinda Kurnia (Babali Publisher, 2020)
Introduction: Patients with diabetic ulcers tend to experience problems in implementing spirituality practices. Patients with diabetic ulcers also experience weaknesses and impaired mobilization that have an impact on family dependence and decreased self-efficacy. The purpose of this study was to determine the relationship between spirituality level and family support with spiritual self-care behavior in diabetic ulcer patients. Methods: A descriptive correlation design with a cross-sectional approach. In a total of 92 patients with diabetic ulcers in Sidoarjo General District Hospital in June-July 2019 recruited. Independent variables were the level of spirituality and family support. The dependent variable was spiritual self-care behavior. Data obtained through the Daily Spiritual Experience Scale (DSES) questionnaire, family support questionnaire, and Spiritual Self Care Practice (SSCPS) questionnaire. Data were analyzed using the Chi-square test of categorical variables with a p-value ≤ 0.05 and logistic regression for multivariate analysis. Results: The study showed there was a significant relationship between spirituality level (p = 0,000) and family support (p = 0,001) with spiritual self-care behavior in diabetic ulcer patients. The result of regression analysis showed the respondents with a high level of spirituality would increase 0.138 times of the spiritual self-care behavior probability. Conclusion: The level of spirituality and family support can promote individual coping to be more positive which may accelerate the process of receiving and healing wounds.